Lifelong learning in Europe equity and efficiency in the balance - Riddell, Sheila 1953-; Markowitsch, Jörg; Weedon, Elisabet ca. 20./21. Jh (Policy Press, 2012)
This timely book contributes to the development of knowledge and understanding of lifelong learning in an expanded Europe. Its wide range of contributors look at the contribution of lifelong learning to economic growth and social cohesion across Europe, focusing its challenge to social exclusion